2015
DOI: 10.1111/sms.12587
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor gene polymorphism influence fat accumulation: A longitudinal study from adolescence to adult age

Abstract: To determine the influence of androgen receptor CAG and GGN repeat polymorphisms on fat mass and maximal fat oxidation (MFO), CAG and GGN repeat lengths were measured in 128 young boys, from which longitudinal data were obtained in 45 of them [mean ± SD: 12.8 ± 3.6 years old at recruitment, and 27.0 ± 4.8 years old at adult age]. Subjects were grouped as CAG short (CAGS) if harboring repeat lengths ≤ 21, the rest as CAG long (CAGL); and GGN short (GGNS) if GGN repeat lengths ≤ 23, or long if > 23 (GGNL). CAGS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
3
9
1
1
Order By: Relevance
“…In agreement, our data revealed that CAG L , who had 21.5% higher levels of free testosterone, also had greater MFO than CAG S , as previously reported in boys followed during 15 years from adolescence to adult age (12). This finding is important since it has been shown in men that low levels of testosterone increase the risk of all-cause and cardiovascular mortality, increase fat accumulation, reduced glucose utilization, glycolysis and mitochondrial oxidative phosphorylation (29), which could affect fatty acid oxidation capacity.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In agreement, our data revealed that CAG L , who had 21.5% higher levels of free testosterone, also had greater MFO than CAG S , as previously reported in boys followed during 15 years from adolescence to adult age (12). This finding is important since it has been shown in men that low levels of testosterone increase the risk of all-cause and cardiovascular mortality, increase fat accumulation, reduced glucose utilization, glycolysis and mitochondrial oxidative phosphorylation (29), which could affect fatty acid oxidation capacity.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast with the present findings, CAG S and GGN S had lower adiposity, fat accumulation than CAG L or GGN L in a longitudinal study from adolescence to adult age (~13 to ~27 years old) (12). Both studies show a beneficial influence of long CAG and GGN repeats on MFO, which could protect against the gain of fat mass over the years.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…It is a master regulator that plays a vital role in the regulation of growth and the protection of endangered breeds. Current studies pay more attention to the function of lipometabolism and cancer, placing almost no focus on animal growth and development (Cameron et al, 2016;Ponce-González et al, 2016;Hu et al, 2017;Recouvreux et al, 2017). Herein, we first confirmed the existence of a novel 24 bp indel (AC_000187.1g.4187270-4187293del AATTTATTGGGAGATTATTGAATT) within the intron of cattle AR genes in four breeds of indigenous cattle.…”
Section: Discussionsupporting
confidence: 63%